2002
DOI: 10.1159/000067067
|View full text |Cite
|
Sign up to set email alerts
|

Grief Hallucinations: True or Pseudo? Serious or Not?

Abstract: An inquiry into the psychopathology and the clinical significance of grief hallucinations is presented and two cases with severe grief hallucinations are described. Unlike many cases in the literature, the two female patients were young (aged 43 and 45, respectively) and both suffered from the loss of a daughter. The heterogeneous concept of grief hallucinations is described and discussed, focusing particularly on the difficulties of reaching a differentiation between hallucination and pseudohallucination. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 17 publications
(27 reference statements)
1
11
0
2
Order By: Relevance
“…As these hallucinatory experiences occur during times of excessive emotion, confusion can come about, often resulting in reports of the person believing their spouse is actually present (Grimby, 1993). Hallucinations occurring out of bereavement have not been found to ascribe to any definitions of pseudo-hallucinations (Baethge, 2002). Similarly, they do not meet any diagnostic criteria for psychological disorders.…”
Section: Hallucinatory Experiences In the Elderlymentioning
confidence: 99%
“…As these hallucinatory experiences occur during times of excessive emotion, confusion can come about, often resulting in reports of the person believing their spouse is actually present (Grimby, 1993). Hallucinations occurring out of bereavement have not been found to ascribe to any definitions of pseudo-hallucinations (Baethge, 2002). Similarly, they do not meet any diagnostic criteria for psychological disorders.…”
Section: Hallucinatory Experiences In the Elderlymentioning
confidence: 99%
“…Hallucinations of a loved one are common following bereavement (4547). They are typically comforting and do not impair functioning (45, 46) (although see (47)); thus, hallucinations may not be abnormal per se . Non-clinical hallucinations also occur in the general population (4852).…”
Section: Introductionmentioning
confidence: 99%
“…One study [51] of bereaved spouses found about half of participants had experienced post bereavement hallucinations, mostly auditory and visual, and sensed the presence of the deceased. A few non-nursing related studies explored grief hallucinations [52,53] and complicated grief [54]. These few studies begin to legitimize an understanding that grief responses can burden persons and manifest in hearing voices.…”
Section: Relevance To Nursingmentioning
confidence: 99%